A Comparative Study on Abstractive Techniques For Text Summarization - Jay Desai, Vishvesh Khandpur, Nimesh Italiya, Aadarsh Ghodasara, Prof. Mrugendra Rahevar (International Journal of Advanced Science and Technology, 2020)
Summarization of data is called “information” but to get the information is somewhat difficult from raw data. This is the task where humans also face issues to get the correct one and so in the era of computers, we need a machine which can easily perform this for us. Here, summarization of data not only includes copying salient and important aspects of the source but also paraphrasing into new sentences that deliver the same message as the source information wants to convey. This paper informs the list of several abstractive summarization methods and after getting a glimpse of every method which are listed from that based on the ROUGE evolution matrices, The best method for abstractive summarization is “Controlling the amount of Verbatim Copying” with respect to other methods discussed here in this paper after the introduction part.